2014
DOI: 10.1021/bi500157z
|View full text |Cite
|
Sign up to set email alerts
|

The Making of a Macromolecular Machine: Assembly of the Membrane Attack Complex

Abstract: The complement terminal pathway clears pathogens by generating cytotoxic membrane attack complex (MAC) pores on target cells. For more than 40 years, biochemical and cellular assays have been used to characterize the lytic nature of the MAC and to define its protein composition. Although models for pore formation have been inferred from structures of bacterial cytolysins, it was only recently that we were able to visualize how complement components come together during MAC assembly. This review highlights stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0
5

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(44 citation statements)
references
References 80 publications
0
39
0
5
Order By: Relevance
“…We further hypothesize that the secreted perforins insert into the epithelial cell membrane to form hetero-oligomeric pores, similar to the hetero-oligomeric membrane attack complex formed by complement proteins C5b-C9 (reviewed in Ref. [38]). Noteworthy, recent data on the PPLP family have shown that these are present in multiple life-cycle stages of the malaria parasite.…”
Section: Resultsmentioning
confidence: 95%
“…We further hypothesize that the secreted perforins insert into the epithelial cell membrane to form hetero-oligomeric pores, similar to the hetero-oligomeric membrane attack complex formed by complement proteins C5b-C9 (reviewed in Ref. [38]). Noteworthy, recent data on the PPLP family have shown that these are present in multiple life-cycle stages of the malaria parasite.…”
Section: Resultsmentioning
confidence: 95%
“…Structural studies show that C5b-8 on the membrane induces conformational changes in CD59 that enable the latter to bind to C9 and inhibit MAC formation (15). Thus, only CD59 on the cell surface can respond to C5b-8, suggesting that sublytic complement attack could modulate CD59 recycling.…”
Section: Resultsmentioning
confidence: 99%
“…The alternative pathway of complement activation begins with the spontaneous hydrolysis of C3 and sequential recruitment of C5b, C6, C7, C8, and finally C9, which polymerizes to form the MAC (2). The membrane-bound complement regulator CD59, which binds C8 and C9, prevents recruitment of C9 to the C5b-8 complex and thus inhibits the final step of MAC assembly (15). Immunostaining of human donor tissue shows that CD59 is predominantly found on the apical surface (16).…”
mentioning
confidence: 99%
“…The complement system was discovered over a century ago by the immunologist Jules Bordet, who described it as the ability of blood plasma factors to lyse bacteria. It is now understood that the complement system involves a cascade of activation reactions that ultimately triggers pore formation by the C9 complement component of the MAC (Bubeck, 2014;Merle et al, 2015). In the 1980s, a related pore-forming protein, perforin, was characterised in cytotoxic T-lymphocytes and natural killer cells in the blood (Podack and Dennert, 1983;McCormack et al, 2013).…”
Section: The Macpf-cdc Superfamilymentioning
confidence: 99%
“…1B). For the MAC, the main pore-forming component C9 binds to the target membrane through a complex that comprises six other MAC componentsC5b (a product of cleavage of C5), C6, C7 and C8 -with the latter comprising the two MACPF proteins C8α and C8β, and the non-MACPF protein C8γ (Bubeck, 2014;Merle et al, 2015). It has been shown that this MAC complex comprising C5b-C8 is capable of forming transmembrane pores and lysing cells in the absence of C9 (Ramm et al, 1982;Morgan et al, 1986), but the structural details and biological relevance of these lesions remain to be understood.…”
Section: Macpf-cdc Pore Formationmentioning
confidence: 99%